Pemberian Konselor Sebaya dalam Upaya Membentuk Perilaku Pencegahan Merokok pada Remaja - Rismalasari Dewi; Nana Supriyatna; Sigit Mulyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine peer counselors' influence in shaping smoking prevention behavior in adolescents in the work area of ​​Kalibaru Public Health Center, Cilincing District, North Jakarta. The method used is a quasi-experimental design with pre-test and post-test, then analyzed with non-parametric statistics using the McNemar test. The subjects of this study were 82 adolescents divided into two groups: the intervention group of 41 adolescents and the control group of 41 adolescents. The research instrument used a questionnaire on smoking prevention behavior, parents' role, peers' influence, and advertising's influence. The results showed that the p-value obtained in the provision of peer counselor intervention on adolescent smoking prevention was 0.000, the role of parents was 0.000, adolescent peers were 0.004 and the effect of advertising on adolescents was 0.000. In conclusion, there is a significant influence of peer counselor intervention on smoking prevention behavior in adolescents. Keywords: Peer Counselor, Smoking, Adolescent